41. HEALTH STAFF'S SATISFACTION AND SOME RELATED FACTORS AT THE NUTRITIONAL COUNSELING DEPARTMENTS AT THE INSTITUTE OF NUTRITION, 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the level of job satisfaction and analyze some factors related to the satisfaction of healthcare staff at the nutritional counseling departments of the Nutrition Institute in 2023.Subject and method: A descriptive cross-sectional survey was conducted to collect quantitative information from 35 healthcare staff at the nutritional counseling departments, using survey forms issued according to Decision 3869/QĐ-BYT dated August 28, 2019, by the Ministry of Health.Results: The average overall satisfaction score was 3.9 ± 0.6. Job satisfaction was lowest in the category of job satisfaction itself, scoring 3.5 ± 0.6, and highest in the category of learning opportunities and career advancement, scoring 4.1 ± 0.6. Only 37.1% of healthcare staff were generally satisfied with the Nutrition Institute's outpatient center. There was a statistically significant difference in satisfaction levels between administrative and professional domains (p < 0.05).Conclusion: Enhancing job satisfaction among healthcare staff in nutritional counseling departments is crucial. This helps improve their work morale, retain them long-term in their positions.
Keywords: Satisfaction; health workers; Institute of Nutrition